The Relationship Between Stock Prices And Exchange Rates : Evidence From Ten Middle Eastern Countries - Parsva, Parham (2012)
This study investigates the relationship between stock prices and exchange rates in ten Middle Eastern countries, namely, Bahrain, Egypt, Iran, Jordan, Kuwait, Lebanon, Oman, Qatar, Saudi Arabia, and the United Arab Emirates (UAE) before and during the 2007 global financial crisis. For this purpose, two frameworks are determined; the first framework is a bivariate model involving only stock prices and exchange rates, while the second framework is a multivariate model including the two relevant variables, inflation rates, and oil prices. Daily data are used for the bivariate model, while monthly data are used for the multivariate model. The sample period is from January 1, 2004 to September 30, 2010. The sample is divided into two subperiods, that is, the period from January 1, 2004 to September 30, 2007 and the period from October 1, 2007 to September 30, 2010, to represent the precrisis period and the crisis period respectively. The econometric techniques employed are unit root tests, Johanson-Juselius cointegration test and Granger causality test. Moreover, to ensure the goodness of fit of the models, some diagnostic and specification tests, that is, serial correlation LM test, Autoregressive Conditional Heteroscedasticity test, and Ramsey’s RESET test, are employed.